Investigating the challenges that impede the viability of a Dental curriculum for Undergraduate studies - Sana Iqbal, Anbreen Aziz, Saher Sultan, Muhammad Azhar, Zubair Ahmed, Maleeha Nayyer (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Perceptions of teachers and students about curriculum viability inhibitors are equally important yet may differ. Divergence can lead to destructive friction and adversely affect curriculum viability. Objectives: Our team aimed to find the perceptions of teachers and students on inhibitors affecting the viability of an implemented medical curriculum, report their convergence or divergence, and explore approaches to reduce divergence. Material and Methods: This is a mixed-method study. For quantitative data, teachers’ perceptions were collected through validated, targeted questionnaires measuring viability inhibitors. For qualitative data, a focus group discussion (FGD) among teachers explored possible approaches to diverging teachers’ perceptions. Results: The data was collected from 53 faculty members (100%). This study provides an approach to measure curriculum viability inhibitors in an undergraduate Dental curriculum, to find solutions of these inhibitors through focus group discussion. No difference in opinion was found in interdepartmental, designation regarding curriculum viability. Years of Experience in different departments affect the choice of assessment tools on the basis of K.S.A. Practical implication: this study will also helpful in improving the curriculum even when no strong inhibitors are present. Conclusion: We believe this approach might help to improve the curriculum, even when no strong inhibitors are present. The suggestions to deal curriculum inhibitors. Questionnaires measuring curriculum viability inhibitors can be used stand-alone or as part of the curriculum evaluation process. Keywords: Mixed method design; teacher perceptions; curriculum viability; curriculum inhibitors.